Pengaruh Model Pembelajaran Kooperatif Tipe STAD dan Jigsaw Terhadap Penguasaan Konsep Fisika - Nur Fadilah Aning Detri; Ni Nyoman Sri Putu Verawati; Satutik Rahayu (Universitas Pendidikan Mandalika, 2018)
[Title: The Effect of STAD and Jigsaw Cooperative Learning Model on the Physics Concepts Mastery]. This research aims to determine the influence of cooperative learning model of STAD and Jigsaw type through physics concept mastery of XI grade students in SMAN 1 Kediri. This type of research is the quasi experimental with posttest only control group design. The population of this research is all students of XI grade in SMAN 1 Kediri of 2018/2019 year of lesson with cluster random sampling taking technique. There are two samples that is the class that given treatment by cooperative learning model STAD’s type (class experiment 1) and class that given treatment by Jigsaw’s type (class experiment 2). The result revealed that the mean score of the post-test for concept mastery for two class in row are 73.69 and 61.07. The two class was homogeny and normal disrtribution. The research hypothesis was tested using t-test polled variances. The result showed that the value of ttab was higher than tarith, (2.841>2.021) at 5% as significancy, that mean H0 rejected and Ha received. Based on result of data analysis and discussion, the conclusion are there was an effect between cooperative learning model STAD and Jigsaw type through physics concept mastery of XI grade students in SMAN 1 Kediri.